2016
DOI: 10.1080/00927872.2015.1065858
|View full text |Cite
|
Sign up to set email alerts
|

Residual Properties of Free Products

Abstract: Let be a class of groups. We give sufficient conditions ensuring that a free product of residually groups is again residually , and analogous conditions are given for LEgroups. As a corollary, we obtain that the class of residually amenable groups and the one of locally embeddable into amenable (LEA) groups are closed under taking free products.Moreover, we consider the pro-topology and we characterize special HNN extensions and amalgamated free products that are residually , where is a suitable class of group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It is easy to see that direct products preserve LEF, and it is known that free products do so too, see Corollary 1.6 in [1]. We obtain the following weaker form of permanence.…”
Section: (I) At Least One Of G or H Is Amenable (Ii) G ∨ H Admits A F...mentioning
confidence: 63%
See 2 more Smart Citations
“…It is easy to see that direct products preserve LEF, and it is known that free products do so too, see Corollary 1.6 in [1]. We obtain the following weaker form of permanence.…”
Section: (I) At Least One Of G or H Is Amenable (Ii) G ∨ H Admits A F...mentioning
confidence: 63%
“…Then G ∨ H = Alt(p + q − 1) still satisfies this property, because its 2-Sylow subgroups have solubility length ≥ 2 (see Theorem 3 in [11]). It follows that (G ∨ H) ∨ J is the alternating group on 1 2 (p + q − 1)! + r − 1 elements, and likewise G ∨ (H ∨ J) on 1 2 (r + q − 1)!…”
Section: Proposition 74 Consider Two Groups G H and A Subgroup K < Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, G#false(1false) is LEF; recall our discussion in Section 2. (Compare with arguments in . )…”
Section: Proof Of Theoremmentioning
confidence: 91%
“…Remark 2. For any property P, if H is not P-separable, then Γ is not residually P. Berlai has shown that for P the properties of solvability and amenability, so long as G is residually P, failure to be P-separable is the only obstruction to Γ being residually P [2].…”
Section: Preliminariesmentioning
confidence: 99%